Precise Characterization and Tracking of Stably Inherited Artificial Minichromosomes Made by Telomere-Mediated Chromosome Truncation in Brassica napus - Yin, Xiangzhen; Zhang, Yingxin; Chen, Yuhong; Wang, Jingqiao; Wang, Richard R.-C.; Fan, Chengming; Hu, Zanmin (Frontiers in Plant Science, 2021)
Plant artificial minichromosomes are the next-generation technology for plant genetic engineering and represent an independent platform for expressing foreign genes and the tools for studying the structure and function of chromosomes. Minichromosomes have been successfully produced by telomere-associated chromosome truncation in several plants. However, previous studies have primarily focused on the construction and rough characterization of minichromosomes, while the development of stably inherited minichromosomes and their precise characterization and tracking over different generations have rarely been demonstrated. In this study, a 0.35-kb direct repeat of the Arabidopsis telomeric sequence was transformed into Brassica napus to produce artificial minichromosomes, which were analyzed by multifluorescence in situ hybridization (multi-FISH), Southern hybridization, and primer extension telomere rapid amplification (PETRA). The stably inherited minichromosomes C2 and C4 were developed by crossing transgenic plants with wild-type plants and then selfing the hybrids. Notably, two truncation sites on chromosomes C2 and C4, respectively, were identified by resquencing; thus, the artificial minichromosomes were tracked over different generations with insertion site-specific PCR. This study provided two stably inherited minichromosomes in oilseed rape and describes approaches to precisely characterize the truncation position and track the minichromosomes in offspring through multi-FISH, genome resequencing and insertion site-specific PCR.